THE COMMUNICATION BARRIERS IN THE HEALTH PROMOTION OF FAMILY PLANNING PROGRAM (KB) IUD IN BANDUNG - Ditha Prasanti (BPSDMP Kominfo Manado, 2018)
Health is the main factor that attracts the public attention today. In an effort to improve the quality of social welfare and public health, the government also conducts health promotion of family planning programs (KB) in various regions. This family planning program has various options, but the government currently being pushed is the use of KB IUD. This health promotion activity also took place in the village of Cimanggu, West Bung. Dinas Kesehatan cooperate with Cimanggu village to conduct health promotion of KB IUD program. But, in fact, the program is not as easy as it thinks. Therefore, the authors raised this study which aims to determine the barriers of communication in the health promotion of Family Planning Program (KB) IUD in Cimanggu village, West Bandung. The research approach is qualitative approach with descriptive method. In determining informant, writer use purposive sampling technique, got 4 person informant. The data collection techniques are observation, interview, and documentation study. The results of the research show that communication barriers in health promotion of IUD family planning program in Cimanggu village, West Bupang Regency cover: (1) education barrier of Cimanggu villagers as communicant in health promotion program of IUD family planning program; (2) cultural barriers of Cimanggu villagers, which are still strong with the values of local wisdom developed in Cimanggu village; (3) psychological barriers, feelings of fear and fear of excessive pain experienced by the society, certainly in this case is women in the productive age.